Surgery for focal cortical dysplasia in drug-resistant epilepsy: case report and literature review - Almagro Allende, Stefania Esther; Berra, Matías; Nieto, Flavia (Revista Argentina de Neurocirugía, 2025)
Background: therapeutic gestures concerning drug-resistant epilepsy provide a scenario where the role of surgery has had a great contribution in recent decades in terms of objectives to be achieved, which are not limited to the complete cessation of seizures but also include the so-called “palliative goal” (conversion to non-refractory epilepsy, reduction of antiepileptic drugs and number of seizures).Objectives: to optimize the diffusion of the pathology and promote early referrals to improve surgical results.Case description: case 1: patient aged 27 years, 5 seizures per week (10 seconds duration), MRI: right frontal lesion hypointense on T1, hyperintense on T2, 3 x 2.25 x 2.84 cm. Case 2: patient aged 60 years, 2-3 seizures per day every 5-8 days (10 minutes duration), MRI: right hippocampal-amygdala lesion hypointense on T1, hyperintense on T2, 2.7 x 2.5 x 1.3 cm.Surgery: case 1: right hemicoronal approach, using electrocorticography complete excision of the lesion was performed without residual epileptogenic tissue. Case 2: right frontotemporal approach with temporal polectomy plus right amygdalohippocampectomy.Conclusion: surgical treatment for epilepsy has undergone a permanent evolution based on a greater understanding of the pathology and advances in imaging techniques. The outlook is encouraging, but there are still delays in referral to a surgical specialist.
Keywords: Drug-resistant epilepsy; Epilepsy surgery; Focal cortical dysplasia; Indications for surgery in epilepsy